2012
DOI: 10.1159/000338979
|View full text |Cite
|
Sign up to set email alerts
|

Role of p16INK4a Cytology Testing as an Adjunct to Enhance the Diagnostic Specificity and Accuracy in Human Papillomavirus-Positive Women within an Organized Cervical Cancer Screening Program

Abstract: Objective: We evaluated the performance of cytologic p16INK4a (p16) immunostaining within a cervical cancer screening program for the categories of atypical squamous cells of undetermined significance (ASC-US) and low-grade squamous intraepithelial lesion (LS after triage with high-risk human papillomavirus (HR-HPV) testing and atypical squamous cells, cannot exclude high-grade intraepithelial squamous lesion (ASC-H) and high-grade squamous intraepithelial lesion (HSIL). We also verified whether the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 52 publications
(33 reference statements)
0
17
0
Order By: Relevance
“…14 Several studies have shown increased sensitivity and specificity for cervical cancer screening using p16 staining in conjunction with other biomarkers, such as p16/Ki-67 15,16,[24][25][26] and Survivin, the inhibitor of apoptosis. 27 …”
Section: ■Discussionmentioning
confidence: 99%
“…14 Several studies have shown increased sensitivity and specificity for cervical cancer screening using p16 staining in conjunction with other biomarkers, such as p16/Ki-67 15,16,[24][25][26] and Survivin, the inhibitor of apoptosis. 27 …”
Section: ■Discussionmentioning
confidence: 99%
“…The detection of p16 INK4a overexpression indicates cellular transformation by high-risk HPV due to cell cycle deregulation. The diagnostic evaluation of p16 INK4a as an individual biomarker was shown to be unreliable in its practical application [23,24,25,26]. An immunocytochemical detection of both p16 INK4a and Ki-67 in the same cell, however, indicates neoplastic cellular transformation [1].…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for the large differences between CIN2 and CIN3 in the distribution of HPV type, as observed in our study, could be the additive use of immunohistochemistry to detect overexpression of the cell cycle protein p16 INK4a for histological grading of CIN lesions. This immunohistochemical method has been shown to improve the accuracy of grading CIN lesions significantly [20,21]. …”
Section: Discussionmentioning
confidence: 99%
“…Cervical neoplasia expresses high levels of p16 INK4a in contrast to other cervical epithelia. This overexpression is linked to oncogenic transformation mediated by persistent hrHPV infection and it has been shown to significantly improve the accuracy of grading CIN lesions [20,21]. …”
Section: Methodsmentioning
confidence: 99%